Genetic Variation in an Experimental Goldfish Derived From Hybridization - Wang, Jing; He, Weiguo; Zeng, Jinfeng; Li, Lixin; Zhang, Guigui; Li, Tangluo; Xiang, Caixia; Chai, Mingli; Liu, Shaojun (Frontiers in Genetics, 2020)
Owning to the extreme difficulty in identifying the primary generation (G0), the common ancestor of various twin-tail goldfish strains remains unclear. However, several authors have hypothesized that this ancestor may have been the crucian carp (Carassius auratus). Previously, we generated an experimental hybrid goldfish (EG) from the interspecific hybridization of red crucian carp (Carassius auratus ♀, RCC) × common carp (Cyprinus carpio ♂, CC). Unlike either parent, EG possessed twin caudal fins similar to those of natural goldfish (Carassius auratus, NG). The genetic characteristics of EG, as well as the mechanisms underlying its formation, are largely unknown. Here, we identified the genetic variation in the chordin gene that was associated with the formation of the twin-tail phenotype in EG: a stop codon mutation at the 127th amino acid. Furthermore, simple sequence repeat (SSR) genotyping indicated that all of the female parent (RCC) alleles were also present in EG, but alleles specific to the male parent (CC) were completely lost. At some loci, EG and NG alleles differed, showing that these morphologically similar goldfish were genetically dissimilar. In addition, phylogenetic analyses based on mitochondrial DNA (mtDNA) recovered EG, NG, and RCC in a single cluster distinct from CC, suggesting that EG fell in the genus Carassius. Collectively, our results demonstrated that genetic variations in EG, in both the chordin gene and the SSR alleles, originated from distant hybridization and contributed to transgressive segregation. This analysis of genetic variation in EG sheds new light on the common ancestor of NG, as well as on the role of hybridization and artificial breeding in NG speciation.